STUDY ON MODE III FRACTURE TOUGHNESS OF ADHESIVE BONDED STRUCTURE - ZHANG ChaoFeng; XIE ChunLi; WANG WeiLi; ZHU JiaJia (Jixie qiangdu)
Failure mode of bonded structure under different adhesive types and different adhesive thickness was discussed by designing the edge ring crack torsion test which can truly reflect mode III fracture toughness. And the fracture characteristies of bonded structure are revealed by combing the peak torque and strain energy release rate. Through the comparative analysis of experiment and simulation, parameter expression of cohesive zone model which considered the thickness effect is deduced by inversion method. The results show that the peak torque and strain energy release rate of Araldite 2015 increased with the increase of adhesive thickness. While the peak torque and strain energy release rate of E-120HP and WD3705 showed a concave trend with the increase of adhesive thickness. This study provides a basis for reasonably evaluating the effect of adhesive type and thickness on the failure mechanism of bonded structures under type III fracture.